1999
DOI: 10.1074/jbc.274.40.28286
|View full text |Cite
|
Sign up to set email alerts
|

12-O-tetradecanoylphorbol-13-acetate-induced Apoptosis Is Mediated by Tumor Necrosis Factor α in Human Monocytic U937 Cells

Abstract: 12-O-tetradecanoylphorbol-13-acetate (TPA), a phorbol ester that is known as a tumor promoter, induces differentiation of myeloid cells and suppresses their proliferation. We studied the regulation of apoptosis by TPA in human monocytic cell line U937 cells that lack p53. Untreated U937 cells constitutively underwent apoptosis, and TPA enhanced apoptosis in these cells. Further studies showed that TPA increased production of tumor necrosis factor-␣ (TNF␣) in U937 cells, and exogenously added TNF␣ induced apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 74 publications
2
33
1
Order By: Relevance
“…Interestingly, TPA-mediated apoptosis has recently been linked to endogenous production of TNF and activation of an auto-or paracrine TNF/TNF-receptor loop, whereas chemotherapy-induced apoptosis can at least in part be a consequence of a Fas/FasL interaction. 21,22 Moreover, we did not observe a protective effect of caspase-8 inhibition prior to TPA treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, TPA-mediated apoptosis has recently been linked to endogenous production of TNF and activation of an auto-or paracrine TNF/TNF-receptor loop, whereas chemotherapy-induced apoptosis can at least in part be a consequence of a Fas/FasL interaction. 21,22 Moreover, we did not observe a protective effect of caspase-8 inhibition prior to TPA treatment.…”
Section: Discussionmentioning
confidence: 72%
“…As the agents which regulate activities of PKC, such as PMA or H-7, caused alteration of the levels of phosphorylated-Bcl10, Bcl10 could be directly phosphorylated by PKC. A variety of reports have suggested that PKC can act as a potentiator of apoptosis induced by stimuli such as TNF (Laouar et al, 1999;Takada et al, 1999). It is possible that Bcl10 might be a novel target molecule involved in the signaling of PKC-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…31,33,50 Likewise, PKCd-induced cell death in HeLa cells and HPVtransformed keratinocytes is presumably p53-independent. 21 In the LNCaP prostate epithelial cell line however, TPA-induced apoptosis was preceded by induction of the cdk inhibitor, p21, and dephosphorylation of the retinoblastoma protein (Rb).…”
Section: Discussionmentioning
confidence: 99%